Comparison of Vaginal pH between Bacterial Vaginosis and Non-bacterial Vaginosis in Preterm Labour - Jiratchaya Kleebsuwan; Chanya Thamrongwuttikul; Watcharin Chirdchim (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objectives: The aim of this study was to compare vaginal discharge pH between bacterial vaginosis (BV) and non-bacterial vaginosis in preterm labour. Materials and Methods: An analytical cross-sectional study was carried out on patients admitted to the obstetrics ward of Prapokklao Hospital from June 2016 to January 2017. The main inclusion criterion was the presence of preterm labour without premature rupture of membranes or vaginal bleeding. Vaginal discharge was collected for pH measurement and Gram stain. The Nugent criteria from the University of British Columbia were used for BV diagnosis.Results: The final analysis was based on data from 105 participants. The prevalence of BV was 71.4%. The mean of vaginal pH was 5.97±0.40 for the BV group and 5.20±0.36 for the non-BV group, z=6.674, p < 0.001. Conclusion: Mean vaginal pH in the BV group was higher than in the non-BV group.